Collegial Collective Decision-Making Mechanisms and Communication - Nofrizal, Nofrizal; Akbar, Bahrullah; Elsye, Rosmery; Khairi, Halilul (Wardah, 2024)
The effectiveness of decision - making is influenced by internal factors such as differences in point of view, conflicts between members, knowledge and experience of team members, trial documentation, and a culture of asking questions and seeking clarification. External influencing factors include pressure from stakeholders, environmental uncertainty, resource availability, and social norms and organizational culture. This study uses a qualitative method with the source of the source data from the speakers and the review of literature and other reading materials. Determination of informants in the study using purposive sampling techniques with data collected through interviews and observations. The location of this study is in the environment of Bawaslu of West Java Province and the structures below it. The Supreme Audit Board (BPK RI) session implements a collective collegial decision-making system, which involves all members of the session in discussion and deliberation to reach a consensus. To improve communication skills and teamwork, BPK RI can take strategic steps such as improving communication skills, creating an open environment, managing conflicts, seeking mutual understanding, and respecting the opinions of members.